2021
DOI: 10.3390/nano11092326
|View full text |Cite
|
Sign up to set email alerts
|

Pd-C Catalytic Thin Films Prepared by Magnetron Sputtering for the Decomposition of Formic Acid

Abstract: Formic acid is an advantageous liquid organic hydrogen carrier. It is relatively nontoxic and can be synthesized by the reaction of CO2 with sustainable hydrogen or by biomass decomposition. As an alternative to more widely studied powdery catalysts, supported Pd-C catalytic thin films with controlled nanostructure and compositions were newly prepared in this work by magnetron sputtering on structured supports and tested for the formic acid decomposition reaction. A two-magnetron configuration (carbon and tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…In previous studies of the FAD reaction, Pd- and Ru-based catalysts were incapable of achieving complete formic acid conversion and 100% H 2 selectivity at once [ 23 , 39 , 58 ]. Arzac et al [ 23 ] prepared a Pd-C thin film supported on a SiC monolith, giving a conversion and selectivity of 80% and 88% at 350 °C, respectively. Selectivities higher than 90% were found at temperatures below 250 °C, with conversion values nearing 20% in dry conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies of the FAD reaction, Pd- and Ru-based catalysts were incapable of achieving complete formic acid conversion and 100% H 2 selectivity at once [ 23 , 39 , 58 ]. Arzac et al [ 23 ] prepared a Pd-C thin film supported on a SiC monolith, giving a conversion and selectivity of 80% and 88% at 350 °C, respectively. Selectivities higher than 90% were found at temperatures below 250 °C, with conversion values nearing 20% in dry conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid—aqueous-phase FAD would help to suppress dehydration reaction, and it has been studied extensively [ 17 , 18 , 19 , 20 , 21 ] although many of these works used homogeneous catalysts that limit the large-scale application of the process [ 22 ]. Regarding gas-phase FAD, it has also been studied [ 23 , 24 , 25 , 26 ], and it has been found that the addition of steam could shift the selectivity towards the dehydrogenation reaction [ 27 ]. Comparing both the liquid- and gas-phase reactions, it seems that the latter may be more attractive from an industrial point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation